Heterogeneous preferences and investments in energy saving measures - Urs Fischbacher; Simeon Schudy; Sabrina Teyssier (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
We investigate whether risk, time, environmental, and social preferences affect single family homeowners' investments in energy efficient renovations and energy quality of their house using established experimental measures and questionnaires. We find that homeowners who report to be more risk taking are more likely to have renovated their house. Pro-environmental and futureoriented renovators, i.e. renovators with lower discount factors, live in homes with higher energy efficiency. Controlling for the energy efficiency of houses, we further find that energy consumption as measured by heating and energy costs are lower for future-oriented and proenvironmental individuals. Social preferences measured in a dictator and a generosity game play a mixed role for investments in energy efficiency and energy consumption.
urn:nbn:de:bvb:19-epub-24894-9
Keywords: C93; D03; Q01; Q50; 330; Risk Preferences; Time Preferences; Environmental Preferences; Social Preferences; Energy Efficiency; Artefactual Field Experiment